Doxycycline induces Hok toxin killing in host E. coli. - Chinwe Uzoma Chukwudi; Liam Good (PLoS ONE)
The antibacterial efficacy of the tetracycline antibiotics has been greatly reduced by the development of resistance, hence a decline in their clinical use. The hok/sok locus is a type I toxin/antitoxin plasmid stability element, often associated with multi-drug resistance plasmids, especially ESBL-encoding plasmids. It enhances host cell survivability and pathogenicity in stressful growth conditions, and increases bacterial tolerance to β-lactam antibiotics. The hok/sok locus forms dsRNA by RNA:RNA interactions between the toxin encoding mRNA and antitoxin non-coding RNA, and doxycycline has been reported to bind dsRNA structures and inhibit their cleavage/processing by the dsRNase, RNase III. This study investigated the antibacterial activities of doxycycline in hok/sok host bacteria cells, the effects on hok/sok-induced changes in growth and the mechanism(s) involved. Diverse strains of E. coli were transformed with hok/sok plasmids and assessed for doxycycline susceptibility and growth changes. The results show that the hok/sok locus increases bacterial susceptibility to doxycycline, which is more apparent in strains with more pronounced hok/sok-induced growth effects. The increased doxycycline susceptibility occurs despite β-lactam resistance imparted by hok/sok. Doxycycline was found to induce bacterial death in a manner phenotypically characteristic of Hok toxin expression, suggesting that it inhibits the toxin/antitoxin dsRNA degradation, leading to Hok toxin expression and cell death. In this way, doxycycline could counteract the multi-drug resistance plasmid maintenance/propagation, persistence and pathogenicity mechanisms associated with the hok/sok locus, which could potentially help in efforts to mitigate the rise of antimicrobial resistance.